Extrinsic Motivation vs. Intrinsic Motivation: Dynamics of Influence on Millennial Generation and Generation Z Employees - Sabila, Jihan; Sisilia, Theresa; Dalimunthe, Ritha (Westscience Press, 2024)
This article reviews literature examining the impact of extrinsic and intrinsic motivation on Millennial and Gen Z employees. As workplaces evolve under the influence of technology and globalization, the work expectations of these two generations continue to shift. This literature review employs a descriptive qualitative approach to evaluate previous studies on extrinsic and intrinsic motivation in Millennials and Gen Z. The primary goal of this approach is to present and synthesize various research findings related to the dynamics of motivation between these two generations. This literature review analyzes research comparing the effectiveness of both types of motivation, evaluating both classic and modern motivational theories, and provides recommendations for human resource managers to effectively manage a multigenerational workforce.